2017
DOI: 10.1371/journal.pntd.0006069
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal antibodies for the detection of Trypanosoma cruzi circulating antigens

Abstract: BackgroundDetection of Trypanosoma cruzi antigens in clinical samples is considered an important diagnostic tool for Chagas disease. The production and use of polyclonal antibodies may contribute to an increase in the sensitivity of immunodiagnosis of Chagas disease.Methodology/Principal findingsPolyclonal antibodies were raised in alpacas, rabbits, and hens immunized with trypomastigote excreted-secreted antigen, membrane proteins, trypomastigote lysate antigen and recombinant 1F8 to produce polyclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These assays detect the residual levels of circulating antigens in blood based on antigen expression and secretion levels, and the half-life of the antigen resulting from typical biological processes such as, degradation, clearance in urine, and sequestration in immune complex or complexed with other globular proteins found in blood. Recently, ELISA using polyclonal antibodies raised against TESA and a trypomastigote lysate were used to detect antigens in plasma and serum samples obtained from patients with CD 18 . Combined with recent advances in single molecule detection using digital ELISA such as the Simoa technology, it is now possible to improve the sensitivity of antigen detection assays by 2-3 orders of magnitude over conventional ELISAs 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assays detect the residual levels of circulating antigens in blood based on antigen expression and secretion levels, and the half-life of the antigen resulting from typical biological processes such as, degradation, clearance in urine, and sequestration in immune complex or complexed with other globular proteins found in blood. Recently, ELISA using polyclonal antibodies raised against TESA and a trypomastigote lysate were used to detect antigens in plasma and serum samples obtained from patients with CD 18 . Combined with recent advances in single molecule detection using digital ELISA such as the Simoa technology, it is now possible to improve the sensitivity of antigen detection assays by 2-3 orders of magnitude over conventional ELISAs 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the drawbacks of current diagnostic assays in establishing treatment efficacy, we and others have shown that it was possible to detect parasite antigens in blood of infected mice and human and discussed the use of these antigen for diagnostic applications and in pre-clinical drug development 18 21 . We reported previously the development of Enzyme Linked Aptamer (ELA) assays to detect T. cruzi excreted secreted antigens (TESA) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…To develop a diagnostic test based on a capture ELISA system, a panel of polyclonal antibodies was produced against membrane antigens or trypomastigote excreted/secreted antigens. The test performed on urine from patients positive for ELISA capture against sera demonstrated a 100% positivity [197]. Antigens are present in urine at low concentrations and are susceptible to degradation after collection.…”
Section: Urinementioning
confidence: 99%
“…These data confirm the persistence of inconclusive results, which, in this study, occurred in both new and returning donors, including those with up to 29 repeatedly non-reactive donations. The search for confirmatory tests, such as the trypomastigote excreted-secreted antigen (TESA)-blot 7 , 8 , 9 , radioimmunoprecipitation assay 10 , 11 and/or application of latent class analysis 12 , that can be routinely used in blood banks to define the exact profile of blood donors with 100% certainty has been the subject of several studies.…”
Section: Introductionmentioning
confidence: 99%